Prayer in the Gospels : a theological exegesis of the ideal pray-er - Nygaard, Mathias (Biblical interpretation series ;, 2012)
In Prayer in the Gospels Mathias Nygaard offers a text-centred reading of the prayer materials of the Gospels. His approach provides for exegesis and theology in a single discussion.